Risk variants and polygenic architecture of disruptive behavior disorders in the context of attention-deficit/hyperactivity disorder - Ditte Demontis (Nature Portfolio, 2021)
ADHD is often found to be comorbid with disruptive behavior disorders, but the genetic loci underlying this comorbidity are unknown. Here, the authors have performed a GWAS meta-analysis of ADHD with disruptive behavior disorders, finding three genome-wide significant loci in Europeans, and replicating one in a Chinese cohort.